A large-size single crystal particle cathode material and preparation method thereof

By adopting specific reactor design and sintering process in the preparation of lithium-ion battery cathode materials, problems such as insufficient size and inconcentrated particle size distribution in the preparation of single-crystal cathode materials are solved, and efficient preparation of large-size single-crystal particle materials is achieved, improving the electrical performance consistency and long-cycle performance of the material.

CN115722174BActive Publication Date: 2025-03-25SVOLT ENERGY TECH (MAANSHAN) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211527197.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-03-25
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

In the prior art, the preparation of single-crystal-particle cathode materials has problems such as insufficient single-crystal particle size, inconcentrated particle size distribution, increased material opposite-element, poor long-cycle performance and poor electrical performance consistency.

Method used

Using a specific reactor design and sintering process, the mineralizer selection and airflow distribution during precursor synthesis and sintering process ensures that the material is sintered in a suspended state, avoids agglomeration, and promotes the growth of single crystal particles.

Benefits of technology

The preparation of large-size single-crystal cathode materials has been achieved, with concentrated particle size, high internal compactness, small specific surface area, good electrical performance consistency of the material, and significantly improved long-cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115722174B_ABST
    Figure CN115722174B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion battery materials, and specifically relates to a large-sized single crystal particle cathode material and a preparation method thereof. The preparation method of the large-sized single crystal particle cathode material provided by the present invention aims at the deficiencies of the prior art, and optimizes the structure design of the precursor synthesis reactor, improves the sintering process additives and the sintering process, so that agglomeration does not occur during the preparation of the material, and the obtained large-sized single crystal particle cathode material has high particle concentration and good consistency of material electrical properties. At the same time, the process technology route can realize large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a large-size single crystal particle cathode material and a preparation method thereof. Background Art

[0002] Lithium batteries are widely used in various fields such as electronic products, automobiles, and aerospace due to their high energy density and good cycle performance. As people have higher and higher requirements for the environmental protection, battery life, and life of lithium-ion batteries, battery design and optimization are becoming more and more important.

[0003] Research has found that the single crystalization of multi-material particles can significantly improve their cycle life and safety performance. This is because polycrystalline materials are secondary particles formed by the aggregation of primary particles of several hundred nanometers; while single crystal materials are directly composed of independent crystals of 2 to 5 microns, and there are no unstable factors such as grain boundaries and interface stress inside, which have high compressive resistance. Larger crystals can well ensure the stability of their structure during the electrochemical cycle, and thus, during the electrochemical cycle, it is not easy to crack, or even peel off the substrate surface, and the pole piece powdering occurs.

[0004] However, the preparation process of single crystal particle cathode materials is very difficult. During the precursor preparation process, higher requirements are placed on crystal nucleation, growth, and intermediate control. If the single crystal control is not high, the material will agglomerate severely after sintering to form secondary particles.

[0005] For example, the prior art discloses a method for synthesizing large single crystal positive electrode materials. On the one hand, the process method only has some requirements on the particle size and specific surface area of ​​the precursor, but does not optimize and improve the crystal formation process and the crystal structure. Such a precursor will first make the material more likely to agglomerate after subsequent sintering. Secondly, the precursor will not be optimized in terms of crystal structure growth, which will affect the subsequent electrical properties such as rate performance, and will have an adverse effect on the long-cycle performance of the material. On the other hand, the method does not particularly optimize the contact between the material and the reaction working gas during the subsequent material sintering process, which will result in insufficient particle concentration of the subsequent sintered material, and the anisotropy of the material will increase, thereby affecting the electrical properties of the material. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the preparation of single crystal particle cathode materials in the prior art, such as the need to further improve the size of single crystal particles, the non-concentrated particle size distribution, the increased anisotropy of the material, which is not conducive to the long-cycle performance of the material, and the poor consistency of the electrical properties of the material, thereby providing a large-size single crystal particle cathode material and a preparation method thereof.

[0007] To this end, the present invention provides the following technical solutions:

[0008] The present invention provides a reactor, comprising a reactor cylinder and a stirring paddle arranged inside, wherein three soluble salt feed ports are arranged around the stirring paddle, and the three soluble salt feed ports are located on the same horizontal plane;

[0009] It also includes two complexing agent feed ports and a precipitating agent feed port, which are alternately arranged with the three soluble salt feed ports, and the two complexing agent feed ports and the precipitating agent feed port are located on the same horizontal plane;

[0010] The bottom of the reactor is provided with a raised flow-guiding structure, which comprises a hemispherical top cover and a cylindrical combination body located between the hemispherical top cover and the bottom of the reactor.

[0011] Optionally, with the stirring shaft of the stirring paddle as the center, the angle between the three soluble salt feed ports is 120°, that is, they are evenly distributed around the periphery of the reactor;

[0012] And / or, the heights of the three soluble salt solution feed ports from the bottom of the reactor are 15-75% of the height of the reactor;

[0013] And / or, with the stirring shaft as the center, the angle between the two complexing agent feed ports and the precipitant feed port is 120°;

[0014] And / or, the heights of the two complexing agent feed ports and the precipitant feed port from the bottom of the reactor are 10-50% of the height of the reactor;

[0015] and / or, the distance between the feed port and the reactor cylinder wall is 5-45% of the reactor inner diameter;

[0016] And / or, the stirring paddle is of double-layer design, the height of the lower paddle from the bottom of the reactor is more than 20% of the height of the reactor, and the distance between the two paddles is 20-65% of the height of the reactor;

[0017] And / or, in the flow-guiding structure, the height of the cylindrical combination is 5-30% of the inner diameter of the reactor;

[0018] and / or, in the flow-guiding structure, the radius of the hemispherical top cover does not exceed 80% of the inner diameter of the reactor;

[0019] And / or, the distance between the edge of the flow-guiding structure and the inner wall of the reactor is 17-83% of the inner diameter of the reactor.

[0020] The present invention also provides a method for preparing a large-size single crystal particle cathode material, using the above-mentioned reactor, comprising the following steps:

[0021] S1, adding a complexing agent and a precipitating agent into a reactor through the two complexing agent feed ports and the precipitating agent feed port, and respectively adding a soluble nickel salt solution, a soluble cobalt salt solution and a soluble manganese salt solution into the reactor through the three soluble salt feed ports, reacting to obtain a precursor;

[0022] S2, mixing the obtained precursor, lithium salt and ore-forming agent, and sintering the materials once in a suspended state; wherein the ore-forming agent is a mixture of γ-alumina or tungsten oxide, phosphate or fluoride, and alkaline copper slag;

[0023] S3, crushing the product after the primary sintering, mixing it with transition metal oxides, and performing secondary sintering on the material in a suspended state.

[0024] The suspended state mentioned in the present invention refers to a state in which solid particles with a specific gravity significantly greater than that of air float in the air without falling or only very little falling under the blowing effect of airflow.

[0025] Optionally, the mass ratio of γ-type alumina or tungsten oxide: phosphate or fluoride: basic copper slag in the ore-forming agent is (0.35-0.65): (0.20-0.45): (0.05-0.20).

[0026] Optionally, in step S1, the reaction temperature in step S1 is 45-75° C., the reaction time is 3-5.5 h, and the stirring speed is 300-850 rpm;

[0027] And / or, the feed flow ratio of one of the complexing agent feed ports to the precipitant feed port is 1:4-4.5:1. The flow ratio is limited to make the two feed ports have a primary and a secondary distinction. When adjusting the reaction, the main feed port can be used when a major adjustment is required, and the auxiliary feed port can be used when a minor adjustment is required, which is conducive to better control of the nucleation and growth of the precursor crystal.

[0028] Optionally, in step S2, the mass ratio of γ-type alumina or tungsten oxide: phosphate or fluoride: basic copper slag in the ore-forming agent is 0.55:0.35:0.1;

[0029] and / or, the molar ratio of lithium element to precursor in the lithium salt is 1.03-1.21:1;

[0030] and / or, the mineralizing agent accounts for 0.1-0.5% of the total weight of the precursor and the lithium salt;

[0031] And / or, the metal oxide is at least one of γ-Al2O3, monoclinic zirconium oxide, yttrium oxide, tungsten oxide, and titanium oxide;

[0032] And / or, the fluoride is at least one of aluminum fluoride, lithium fluoride, aluminum fluoride, and sodium fluoride;

[0033] and / or, at least one of the phosphates Mg3(PO4)2, Zn3(PO4)2, Al3(PO4)2, FePO4;

[0034] And / or, in step S3, the amount of transition metal oxide added can be determined according to the modification requirements, for example, based on the total mass of the cathode material, the amount of transition metal oxide added is 100 ppm-10000 ppm;

[0035] And / or, the transition metal oxide is conventionally selected in the field, for example, it can be at least one of MoO3, ZrO, CeO, Al2O3, TiO2, and NbO.

[0036] Optionally, in step S2, the primary sintering temperature is 650-850° C. and the time is 6-16 hours;

[0037] and / or, in a non-suspended state, the material thickness is 35-60 mm.

[0038] Optionally, in step S3, the secondary sintering temperature is 300-550° C. and the time is 3-10 hours;

[0039] and / or, in a non-suspended state, the material thickness is 35-55 mm.

[0040] Optionally, in step S2 and step S3, the material is suspended by airflow;

[0041] and / or, the oxygen volume concentration in the gas flow is between 65.5% and 99.5%;

[0042] And / or, the flow rate of the airflow is above 3 L / min, optionally, the flow rate of the airflow is 3-15 L / min.

[0043] The present invention also provides a large-size single crystal particle cathode material prepared by the above-mentioned preparation method;

[0044] Optionally, the cathode material has a particle size of 6-13 μm.

[0045] The soluble salts, complexing agents, and precipitants used in the preparation process of the cathode material precursor are all conventional materials in the field. Typically, the soluble manganese salt is at least one of manganese sulfate, manganese nitrate, and manganese chloride; the soluble nickel salt is at least one of nickel sulfate, nickel nitrate, and nickel chloride; the soluble cobalt salt is at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride; the concentration of the soluble salt solution can be 1-2 mol / L, and the flow rate is 1-1.5 L / min; the complexing agent is at least one of ammonia water, and its concentration can be 0.5-2 mol / L, and the total flow rate is 1.5-2.5 L / min; the precipitant is at least one of caustic soda and potassium hydroxide solution, and its concentration can be 0.2-1.5 mol / L, and the flow rate is 0.3-0.8 L / min.

[0046] The usage ratio of the above materials is determined according to the product model or requirements. Typically, but not limiting, the molar ratio of the elements is Ni:Co:Mn=1:1:1 or 5:2:3 or 6:2:2 or 8:1:1.

[0047] The lithium salt used in the sintering process is a conventional material in the field. Typically, but not limiting, the lithium salt is at least one of lithium hydroxide monohydrate and lithium carbonate.

[0048] In order to further improve the uniformity of working gas distribution during sintering and increase gas utilization, the gas inlet can be divided into multiple inlet channels, such as Figure 5 As shown, the form has five air intakes (two are not shown) and are symmetrically distributed. More air intakes or other symmetrical and asymmetrical forms can also be set based on this idea, but are not limited to this.

[0049] The technical solution of the present invention has the following advantages:

[0050] The reactor provided by the present invention can achieve a better mixing effect by setting the position of the feed port and designing the flow guide structure at the bottom of the reactor. For example, when the stirring paddle stirs the fluid, the slurry fluid is pushed to the bottom of the reactor. After the fluid encounters the spherical protrusion structure, it will be evenly dispersed around the bottom of the reactor. Then the fluid will be mixed upward along the cylinder wall to form a periodic up and down circular motion, so that the slurry can achieve a better mixing effect. The cathode material precursor synthesized by the reactor provided by the present invention has a high concentration of particle size distribution, D50 is 5.5-12.5μm, the internal compactness of the particles is high, and the BET is relatively small.

[0051] The reactor provided by the present invention can further enhance the mixing effect and thus improve various properties of the precursor material by limiting its specific parameters.

[0052] The method for preparing a large-sized single crystal particle cathode material provided by the present invention aims at the deficiencies in the prior art. By optimizing the structural design of the precursor synthesis reactor, improving the sintering process additives and the sintering process, etc., agglomeration will not occur during the preparation of the material. The obtained large-sized single crystal particle cathode material has high particle concentration and good consistency of material electrical properties. At the same time, this process technology route can be applied on a large scale in industrial applications. Specifically, the cathode material precursor synthesized by the reactor provided by the present invention has a high concentration of particle size distribution, D50 is 5.5-12.5μm, the internal compactness of the particles is high, the BET is relatively small, and agglomeration will not occur during the subsequent sintering process, which is conducive to the growth of single crystal particles; by adopting a specific sintering process and selecting a mineralizing agent, the crystal isotropy during the material growth process can be better, agglomeration can be avoided, and the crystal growth time is greatly shortened due to the more complete and uniform contact between the gas and the material; the pressure generated by the airflow lifts and suspends the aforementioned mixed material, and the particle gap is significantly increased compared with the traditional sintering process. At the same time, by adjusting the ventilation volume, the particles can be in a weak contact state, and the oxygen-rich atmosphere can be evenly distributed between the materials in the reactor without obvious gradient differences, optimizing the particle dispersion, avoiding agglomeration, so that the cathode material finally obtained has a uniform crystal structure, better crystal isotropy, is in a single grain state, D50 is 6-13μm, and the material has a large-size single crystal material with good consistency in electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 It is a schematic diagram of the structure of the reactor provided by the present invention;

[0055] Figure 2 is a top view of the reaction kettle provided by the present invention;

[0056] Figure 3 is a schematic diagram of the flow guide structure in the reactor;

[0057] Figure 4 is a schematic structural diagram of a sintering device used in an embodiment of the present invention;

[0058] Figure 5 is a schematic structural diagram of a sintering device used in an embodiment of the present invention;

[0059] Figure 6 is a SEM image of the precursor obtained in Example 1 of the present invention;

[0060] Figure 7 This is a SEM image of the cathode material of large-sized single crystal particles obtained in Example 1 of the present invention.

[0061] Figure 8 is a SEM image of the cathode material obtained in Comparative Example 2 of the present invention;

[0062] Fig. 9 This is a SEM image of the cathode material obtained in Comparative Example 3 of the present invention.

[0063] Reference numerals:

[0064] 1. Soluble salt feed port; 2. Complexing agent feed port; 3. Precipitant feed port; 4. Stirring shaft; 5. Stirring paddle; 6. Cylindrical combination; 7. Hemispherical top cover; 8. Air inlet; 9. Air outlet; 10. Porous material tray. DETAILED DESCRIPTION

[0065] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0066] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0067] Example 1

[0068] This embodiment provides a large-size single crystal particle cathode material, and the specific preparation method thereof is as follows:

[0069] The structure of the reactor used for precursor preparation is as follows: Figure 1-3As shown, the distance between the three soluble salt feed ports 1 in the reactor and the bottom of the reactor is set to 55% of the total height of the reactor, and the distance between the three soluble salt feed ports 1 and the reactor barrel wall is set to 30% of the inner diameter of the reactor (here refers to the diameter, the same below), and the configuration concentration of the three salt solutions of manganese sulfate, cobalt sulfate, and nickel sulfate is 1 mol / L, and they enter the reactor at a flow rate of 1.2 L / min at the same time; the distance between the complexing agent feed port 2 and the precipitant feed port 3 and the bottom of the reactor accounts for 20% of the total height of the reactor, wherein the feed flow ratio of the two complexing agent feed ports is 1:2.5, the total feed flow rate of the complexing agent is 1.8 L / min, and the feed flow rate of the precipitant is The stirring speed is 550 rpm, wherein, with the stirring shaft as the center, the angle between the three soluble salt feed ports is 120°, the angle between the two complexing agent feed ports and the precipitant feed port is also 120°, and the two blades of the stirring paddle 5 are in the form of inclined blades, the spacing between which accounts for 37% of the total height of the reactor, and the distance between the lower blade and the bottom of the reactor is 28% of the total height of the reactor. The blades should be downward pressure type, the purpose is to make the liquid tend to move to the bottom of the reactor. The radius of the hemispherical top cover 7 at the bottom of the reactor is 25% of the inner diameter of the reactor, the height of the cylindrical combination 6 connected to the hemispherical top cover is 15% of the inner diameter of the reactor, and the distance from the edge of the bottom guide structure to the inner wall of the reactor is 28% of the inner diameter of the reactor. After the reaction is completed, a centrifuge is used to separate the products to obtain the cathode material precursor (Ni 1 / 3 Co 1 / 3Mn 1 / 3 (OH)2). The precursor produced by the above method is as follows Figure 6 As shown, the interior of the particles is radial, which is conducive to the embedding of lithium ions in the subsequent sintering process, and the precursor particle size D50 is 8.9μm.

[0070] The above precursor, lithium salt (lithium carbonate), and ore-forming agent (specifically composed of aluminum oxide, magnesium fluoride, and alkaline copper slag in a mass ratio of 0.55:0.35:0.1) were mixed evenly in a mass ratio of 2.1:1:0.011 and then sintered for the first time at 697°C for 11 hours. The sintering process was performed using the following apparatus: Figure 4 As shown, the material is arranged on a porous material tray 10 inside the sintering device, and the material layer thickness (when the bottom is not blown up) is controlled at 40±3mm. During the sintering process, an oxygen gas flow with a volume concentration of 96% is introduced from the air inlet 8, and the ventilation volume is 12L / min to keep the material in a suspended state (or fluidized state). Exhaust ports 9 are provided on the top of the device in a symmetrical distribution.

[0071] The material obtained by the first sintering is crushed by mechanical grinding to a particle size of 8-9um, and then mixed with ZrO powder for a second time. The amount of ZrO powder added is 2500ppm. The mixed material is sintered for a second time again. The sintering device shown in the previous step is used. The sintering temperature is 475℃, and the material layer thickness (when the bottom is not blown up) is set to 45±3mm. The sintering is carried out for 5 hours. During the sintering process, an oxygen volume concentration of 80% is introduced. The ventilation volume is 8L / min to make the material in a suspended state (or fluidized state). Finally, a single crystal cathode material with a particle size of about 9.3um can be obtained. Figure 7 As shown in the figure, it can be seen that the material has no agglomeration and the particle size is uniform.

[0072] Example 2

[0073] This embodiment provides a large-size single crystal particle cathode material, and the specific preparation method thereof is as follows:

[0074] The structure of the reactor used for precursor preparation is as follows: Figure 1-3 As shown, the distance between the three soluble salt feed ports 1 in the reactor and the bottom of the reactor is set to 63% of the total height of the reactor, and the distance between the three soluble salt feed ports 1 and the reactor barrel wall is set to 23% of the inner diameter of the reactor. The configuration concentration of the three salt solutions of manganese sulfate, cobalt sulfate, and nickel sulfate is 1.6 mol / L, and they enter the reactor at a flow rate of 1.35 L / min at the same time; the distance between the complexing agent feed port 2 and the precipitant feed port 3 and the bottom of the reactor accounts for 27% of the total height of the reactor, wherein the feed flow ratio of the two complexing agent feed ports is 3.25:1, the total feed flow rate of the complexing agent is 2.1 L / min, and the feed flow rate of the precipitant is 0.58 L / min, When preparing the precursor, a certain amount of complexing agent ammonia water (concentration of 0.8 mol / L) and precipitant potassium hydroxide (concentration of 1.1 mol / L) solution are first added into the reactor to form a suitable reaction bottom solution, and then three salt solutions are introduced, and the reaction is carried out at 58°C for 3.5 hours, and the stirring speed is 550 rpm, wherein, with the stirring shaft as the center of the circle, the angle between the three soluble salt feed ports is 120°, the angle between the two complexing agent feed ports and the precipitant feed port is also 120°, and the two blades of the stirring paddle 5 are six-fold blade open turbine forms, and the spacing between them accounts for 29% of the total height of the reactor, and the distance between the lower blade and the bottom of the reactor is 24% of the total height of the reactor. The radius of the hemispherical top cover 7 at the bottom of the reactor is 32% of the inner diameter of the reactor, the height of the cylindrical combination 6 connected to the hemispherical top cover 7 is 18% of the inner diameter of the reactor, and the distance between the edge of the bottom guide structure of the reactor and the inner wall of the reactor is 34% of the inner diameter of the reactor. After the reaction is completed, the product is separated by a centrifuge to obtain a cathode material precursor. The precursor produced by the above method has a particle size D50 of 10.7 μm.

[0075] The above precursor, lithium salt (lithium carbonate), and ore-forming agent (specifically composed of aluminum oxide, magnesium phosphate, and alkaline copper slag in a mass ratio of 0.4:0.4:0.2) were mixed evenly in a mass ratio of 2.05:1:0.013 and then sintered for the first time at 735°C for 12.5 hours. The sintering process was performed using the following apparatus: Figure 4 As shown, the material is arranged on a porous material tray 10 inside the sintering device, and the material layer thickness (when the bottom is not blown up) is controlled at 40±3mm. During the sintering process, an oxygen gas flow with a volume concentration of 98% is introduced from the air inlet 8, and the ventilation volume is 16L / min to keep the material in a suspended state (or fluidized state). Exhaust ports 9 are provided on the top of the device in a symmetrical distribution.

[0076] The material obtained by the first sintering is crushed by mechanical grinding to a particle size of 8-9μm, and then mixed with MgO powder for a second time. The addition amount of MgO powder is 5500ppm. The mixed material is sintered for a second time. The sintering device shown in the previous step is used. The sintering temperature is 515℃, and the material layer thickness (when the bottom is not blown up) is set to 45±3mm. The sintering is carried out for 6 hours. During the sintering process, an oxygen volume concentration of 88% air flow is introduced, and the ventilation volume is 10L / min to keep the material in a suspended state (or fluidized state). Finally, a single crystal cathode material with a particle size of about 11.4um can be obtained.

[0077] Example 3

[0078] This embodiment provides a large-size single crystal particle cathode material, and the specific preparation method thereof is as follows:

[0079] The structure of the reactor used for precursor preparation is as follows: Figure 1-3As shown, the distance between the three soluble salt feed ports 1 in the reactor and the bottom of the reactor is set to 55% of the total height of the reactor, and the distance between the three soluble salt feed ports 1 and the reactor barrel wall is set to 20% of the inner diameter of the reactor. The configuration concentration of the three salt solutions of manganese sulfate, cobalt sulfate, and nickel sulfate is 1 mol / L, and they enter the reactor at a flow rate of 1.2 L / min at the same time; the distance between the complexing agent feed port 2 and the precipitant feed port 3 and the bottom of the reactor accounts for 20% of the total height of the reactor, wherein the feed flow ratio of the two complexing agent feed ports is 1:4, the total feed flow rate of the complexing agent is 1.8 L / min, and the feed flow rate of the precipitant is 0.45 L / min When preparing the precursor, a certain amount of complexing agent ammonia water (concentration of 1.5 mol / L) and precipitant caustic soda (concentration of 1.3 mol / L) solution are first added into the reactor to form a suitable reaction bottom solution, and then three salt solutions are introduced, and the reaction is carried out at 55°C for 3 hours, and the stirring speed is 550 rpm, wherein the angle between the three soluble salt feed ports is 120° with the stirring shaft as the center of the circle, and the angle between the two complexing agent feed ports and the precipitant feed port is also 120°, and the two blades of the stirring paddle 5 are in the form of oblique blades, and the spacing between them accounts for 25% of the total height of the reactor, and the distance between the lower blade and the bottom of the reactor is 22% of the total height of the reactor. The radius of the hemispherical top cover 7 at the bottom of the reactor is 25% of the inner diameter of the reactor, the height of the cylindrical combination 6 connected to the hemispherical top cover is 15% of the inner diameter of the reactor, and the distance between the edge of the bottom guide structure of the reactor and the inner wall of the reactor is 28% of the inner diameter of the reactor. After the reaction is completed, a centrifuge is used to separate the products to obtain a cathode material precursor with a particle size D50 of 5.7 μm.

[0080] Then, the above precursor, lithium salt (lithium hydroxide monohydrate), and ore-forming agent (specifically composed of tungsten oxide + aluminum fluoride + acid copper slag, with a mass ratio of 0.6:0.25:0.15) were uniformly mixed according to a mass ratio of 2.09:1:0.013 and then sintered for the first time at 713°C for 12 hours. The device used in the sintering process is as follows: Figure 5 As shown, the material is arranged on a porous material tray 10 inside the sintering device, and the material layer thickness (when the bottom is not blown up) is controlled at 35±3mm. During the sintering process, an oxygen gas flow with a volume concentration of 96% is introduced from the air inlet 8, and the ventilation volume is 12L / min to keep the material in a suspended state (or fluidized state). Exhaust ports 9 are provided on the top of the device in a symmetrical distribution.

[0081] The material obtained by the first sintering was crushed to 6-6.5um by air flow, and then mixed with ZrO powder for a second time. The amount of ZrO powder added was 1500ppm. The mixed material was sintered for a second time. The sintering device shown in the previous step was used. The sintering temperature was 505℃, and the material layer thickness (when the bottom was not blown up) was set to 50±3mm. The sintering was performed for 6 hours. During the sintering process, an oxygen volume concentration of 92% was introduced. The ventilation volume was 11L / min to make the material in a suspended state (or fluidized state). Finally, a single crystal cathode material with a particle size of about 6.2um was obtained.

[0082] Example 4

[0083] This embodiment provides a large-size single crystal particle cathode material, and the specific preparation method thereof is as follows:

[0084] The structure of the reactor used for precursor preparation is as follows: Figure 1-3 As shown, the distance between the three soluble salt feed ports 1 in the reactor and the bottom of the reactor is set to 70% of the total height of the reactor, and the distance between the three soluble salt feed ports 1 and the reactor barrel wall is set to 40% of the inner diameter of the reactor. The configuration concentration of the three salt solutions of manganese sulfate, cobalt sulfate, and nickel sulfate is 1.15 mol / L, and they enter the reactor at a flow rate of 1.5 L / min at the same time; the distance between the complexing agent feed port 2 and the precipitant feed port 3 and the bottom of the reactor accounts for 20% of the total height of the reactor, wherein the feed flow ratio of the two complexing agent feed ports is 1:1, the total feed flow rate of the complexing agent is 2.1 L / min, and the feed flow rate of the precipitant is 0.67 L / min, when preparing the precursor, first add a certain amount of complexing agent ammonia water (1mol / L) and precipitant caustic soda solution (0.8mol / L) into the reactor to form a suitable reaction bottom solution, and then introduce three salt solutions, react at 60°C for 3 hours, and stir at a speed of 750 rpm, wherein, with the stirring shaft as the center of the circle, the angle between the three soluble salt feed ports is 120°, the angle between the two complexing agent feed ports and the precipitant feed port is also 120°, the two blades of the stirring paddle 5 are in the form of oblique blades, the spacing between them accounts for 35% of the total height of the reactor, and the distance between the lower blade and the bottom of the reactor is 28% of the total height of the reactor. The radius of the hemispherical top cover 7 at the bottom of the reactor is 25% of the inner diameter of the reactor, the height of the cylindrical combination 6 connected to the hemispherical top cover is 15% of the inner diameter of the reactor, and the distance between the edge of the bottom guide structure of the reactor and the inner wall of the reactor is 28% of the inner diameter of the reactor. After the reaction is completed, a centrifuge is used to separate the products to obtain a cathode material precursor. The precursor particles produced by the above method are radial inside, which is conducive to the embedding of lithium ions in the subsequent sintering process. The precursor particle size D50 is 12.2μm.

[0085] The above precursor, lithium salt (lithium hydroxide monohydrate), and ore-forming agent (specifically, aluminum oxide + magnesium fluoride + copper slag, with a mass ratio of 0.4:0.4:1) were mixed uniformly according to a mass ratio of 2.1:1:0.011 and then sintered for the first time at 707°C for 11 hours. The sintering process was performed using the following apparatus: Figure 4 As shown, the material is arranged on a porous material tray 10 inside the sintering device, and the material layer thickness (when the bottom is not blown up) is controlled at 40±3mm. During the sintering process, an oxygen gas flow with a volume concentration of 95% is introduced from the air inlet 8, and the ventilation volume is 15L / min to keep the material in a suspended state (or fluidized state). Exhaust ports 9 are provided on the top of the device in a symmetrical distribution.

[0086] The material obtained by the first sintering was crushed to 12-13um by air flow, and then mixed with MgO powder for a second time. The amount of MgO powder added was 1000ppm. The mixed material was sintered for a second time. The sintering device shown in the previous step was used. The sintering temperature was 525℃, and the material layer thickness (when the bottom was not blown up) was set to 45±3mm. The sintering was performed for 5 hours. During the sintering process, an oxygen volume concentration of 80% was introduced. The ventilation volume was 8L / min to make the material in a suspended state (or fluidized state). Finally, a single crystal cathode material with a particle size of about 12.6um was obtained.

[0087] Comparative Example 1

[0088] Compared with Example 1, a conventional reactor is used, there is no guide structure at the bottom, the complexing agent feed port is a single feed port, the feed ports of the salt solution and the precipitant and complexing agent are in the same plane, the obtained precursor particle size distribution is not concentrated enough, and the morphology of the single crystal material obtained by sintering is not good.

[0089] The following is a conventional reactor structure: the distance between the three soluble salt feed ports and the bottom of the reactor used in the precursor preparation is set to 35% of the total height of the reactor, the distance between the three soluble salt feed ports and the reactor barrel wall is set to 20% of the inner diameter of the reactor, the three salt feed ports are 2 cm apart from each other, the complexing agent feed port and the precipitant feed port are set on the opposite side of the three salt solution feed ports, and other parameters are the same as in Example 1. The precursor particle size D10 produced by the above method is 1.7μm, D50 is 5.8μm, and D90 is 15.7μm. Finally, a single crystal cathode material with a particle size of about 6.6um can be obtained, and the single crystal morphology of the material is not good.

[0090] Comparative Example 2

[0091] Compared with Example 1, a conventional sintering method and a conventional ventilation method (non-fluidized state) are adopted. The specific operations during the sintering process are:

[0092] For the first sintering, the material was sintered in an ordinary box furnace for 11 hours, and the material layer thickness was 40±3 mm. During the sintering process, an oxygen volume concentration of 96% was introduced, and the ventilation volume was 12 L / min.

[0093] The second sintering was still carried out in a box furnace, with a sintering temperature of 475°C, a material layer thickness of 45±3mm, and a sintering time of 5 hours. During the sintering process, an oxygen gas flow with a volume concentration of 80% was introduced, and the ventilation volume was 8L / min. A cathode material with a particle size of about 8.1um was obtained. Although the material was a single crystal, it was severely agglomerated and had poor dispersion. Figure 8 shown.

[0094] Comparative Example 3

[0095] Compared with Example 1, the difference is that conventional ore-forming agent Al2O3 is used instead of the ore-forming agent in Example 1. The particle size D50 of the prepared precursor is 8.9 μm; the cathode material with a particle size of about 9.2 μm is obtained, but the single crystal state is not good, similar to secondary balls, and the agglomeration is serious and the dispersion is not good. Fig. 9 shown.

[0096] Test Case

[0097] The samples provided in the embodiments and comparative examples were tested, including the primary particle distribution, particle size distribution and agglomeration of the materials. The specific testing method is as follows:

[0098] 1. Primary particle distribution (i.e. anisotropy): Count the primary particle size under a scanning electron microscope;

[0099] 2. Particle size distribution: tested by Malvern laser particle size tester;

[0100] 3. Agglomeration: The morphology was observed using a scanning electron microscope;

[0101] The specific test results are as follows:

[0102] Table 1

[0103]

[0104]

[0105] Note: Example 1 and Comparative Examples 2 and 3 use the same batch of precursors, so the precursor particle size and specific surface area data are consistent.

[0106] From the data in the above table, it can be seen that the precursor synthesized by the technology proposed in the present invention has a narrow particle size distribution, and after sintering, it can form large-sized single crystal particles with narrow particle size distribution and no agglomeration. By comparing the data of the embodiment with the comparative example, it can be seen that the structural design of the precursor synthesis reactor, the adjustment of the sintering process, and the selection of the mineralizing agent during the sintering process directly affect the agglomeration degree and particle size distribution of the product.

[0107] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a large-size single crystal particle cathode material, characterized in that: The steps include: S1, adding a complexing agent and a precipitating agent into a reactor through two complexing agent feed ports and a precipitating agent feed port, and adding a soluble nickel salt solution, a soluble cobalt salt solution and a soluble manganese salt solution into the reactor through three soluble salt feed ports, respectively, to react and obtain a precursor; S2, mixing the obtained precursor, lithium salt and ore-forming agent, and sintering the materials once in a suspended state; wherein the ore-forming agent is a mixture of γ-alumina or tungsten oxide, phosphate or fluoride, and alkaline copper slag; S3, crushing the product after the primary sintering, mixing it with transition metal oxides, and performing secondary sintering on the material in a suspended state; The reactor comprises a reactor cylinder and a stirring paddle arranged inside, three soluble salt feed ports are arranged around the stirring paddle, and the three soluble salt feed ports are located on the same horizontal plane; It also includes two complexing agent feed ports and a precipitating agent feed port, which are alternately arranged with the three soluble salt feed ports, and the two complexing agent feed ports and the precipitating agent feed port are located on the same horizontal plane; The bottom of the reactor is provided with a raised flow-guiding structure, which comprises a hemispherical top cover and a cylindrical combination body located between the hemispherical top cover and the bottom of the reactor.

2. The method for preparing a large-size single crystal particle cathode material according to claim 1, characterized in that: With the stirring shaft of the stirring paddle as the center, the angle between the three soluble salt feed ports is 120°; And / or, the heights of the three soluble salt feed ports from the bottom of the reactor are 15%-75% of the height of the reactor; And / or, with the stirring shaft as the center, the angle between the two complexing agent feed ports and the precipitant feed port is 120°; And / or, the heights of the two complexing agent feed ports and the precipitant feed port from the bottom of the reactor are 10%-50% of the height of the reactor; and / or, the distance between the feed port and the reactor cylinder wall is 5-45% of the reactor inner diameter; And / or, the stirring paddle is of double-layer design, the height of the lower paddle from the bottom of the reactor is more than 20% of the height of the reactor, and the distance between the two paddles is 20%-65% of the height of the reactor; And / or, in the flow-guiding structure, the height of the cylindrical combination is 5%-30% of the inner diameter of the reactor; and / or, in the flow-guiding structure, the radius of the hemispherical top cover does not exceed 80% of the inner diameter of the reactor; And / or, the distance between the edge of the guide structure and the inner wall of the reactor is 17%-83% of the inner diameter of the reactor.

3. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: The mass ratio of gamma-type alumina or tungsten oxide: phosphate or fluoride: basic copper slag in the ore-forming agent is (0.35-0.65): (0.20-0.45): (0.05-0.20).

4. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: The reaction temperature in step S1 is 45-75°C, the reaction time is 3-5.5h, and the stirring speed is 300-850 rpm; And / or, the feed flow ratio between one of the complexing agent feed ports and the precipitating agent feed port is 1:4-4.5:

1.

5. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: In step S2, the mass ratio of γ-type alumina or tungsten oxide: phosphate or fluoride: basic copper slag in the ore-forming agent is 0.55:0.35:0.1; and / or, the molar ratio of lithium element to precursor in the lithium salt is 1.03-1.21:1; and / or, the mineralizing agent accounts for 0.1-0.5% of the total weight of the precursor and the lithium salt; And / or, the fluoride is at least one of aluminum fluoride, lithium fluoride, aluminum fluoride, and sodium fluoride; and / or, the phosphate is at least one of Mg3(PO4)2, Zn3(PO4)2, Al3(PO4)2, and FePO4; and / or, in step S3, the amount of transition metal oxide added is 100 ppm-10000 ppm based on the total mass of the cathode material; And / or, the transition metal oxide is at least one of MoO3, ZrO, CeO, Al2O3, TiO2, and NbO.

6. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: In step S2, the primary sintering temperature is 650-850° C. and the time is 6-16 hours; and / or, in a non-suspended state, the material thickness is 35-60 mm.

7. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: In step S3, the secondary sintering temperature is 300-550°C and the time is 3-10 hours; and / or, in a non-suspended state, the material thickness is 35-55 mm.

8. The method for preparing a large-size single crystal particle cathode material according to claim 1 or 2, characterized in that: In step S2 and step S3, the material is suspended by air flow; and / or, the oxygen volume concentration in the gas flow is between 65.5% and 99.5%; And / or, the flow rate of the airflow is above 3 L / min.

9. The method for preparing a large-size single crystal particle cathode material according to claim 8, characterized in that: The flow rate of the air flow is 3-15 L / min.

10. A large-sized single crystal particle cathode material prepared by the preparation method according to any one of claims 1 to 9.

11. The large-size single crystal particle cathode material according to claim 10, characterized in that: The particle size of the cathode material is 6-13 μm.

Citation Information

Patent Citations

  • Preparation method of large-particle precursor for lithium ion battery anode material

    CN108264097A

  • Single crystal lithium-rich manganese-based anode material, preparation method thereof, lithium ion battery

    CN108598457A

  • Vertical reaction kettle with temperature control function

    CN203990634U

  • Pharmaceutical reaction kettle feeding device

    CN211411958U

  • Large glass fiber reinforced plastic reaction kettle for producing acidified oil

    CN212237239U